2014
DOI: 10.1002/nbm.3136
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized gas diffusion MRI for the study of atelectasis and acute respiratory distress syndrome

Abstract: Considerable uncertainty remains about the best ventilator strategies for the mitigation of atelectasis and associated airspace stretch in patients with acute respiratory distress syndrome (ARDS). In addition to several immediate physiological effects, atelectasis increases the risk of ventilator-associated lung injury (VALI), which has been shown to significantly worsen ARDS outcomes. A number of lung imaging techniques have made substantial headway in clarifying the mechanisms of atelectasis. This paper revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…Similarly, Seah et al showed that over-distension caused by high Vt did not cause lung histopathology unless it was combined with high dynamic strain when PEEP is set at zero [ 42 , 43 ]. Using a novel method of polarized gas inhalation, which can identify the dynamic change in structures as small as alveoli and alveolar ducts, it was shown that increasing lung volume with PEEP actually decreased alveolar size, while increasing alveolar number [ 44 ]. Thus, the ‘hyper-inflated’ lung tissue seen on CT might not be caused by over-distended alveoli but rather by an increase in the number of smaller, newly recruited alveoli.…”
Section: Reviewmentioning
confidence: 99%
“…Similarly, Seah et al showed that over-distension caused by high Vt did not cause lung histopathology unless it was combined with high dynamic strain when PEEP is set at zero [ 42 , 43 ]. Using a novel method of polarized gas inhalation, which can identify the dynamic change in structures as small as alveoli and alveolar ducts, it was shown that increasing lung volume with PEEP actually decreased alveolar size, while increasing alveolar number [ 44 ]. Thus, the ‘hyper-inflated’ lung tissue seen on CT might not be caused by over-distended alveoli but rather by an increase in the number of smaller, newly recruited alveoli.…”
Section: Reviewmentioning
confidence: 99%
“…Tomographic lung imaging (e.g., including CT, positron emission tomography [PET], and electrical impedance tomography [EIT]), magnetic resonance imaging (MRI), and lung ultrasound (LUS) provide useful data to improve strategies to prevent VILI. 241 242 As lung monitoring by lung imaging is not specifically part of this chapter, we refer—for the reader—to the most updated guidelines or leading reports detailing the potential of lung imaging in the diagnostics and in the evaluation of the lung injury severity through CT, 143 PET, 243 EIT, 244 MRI, 245 246 and LUS. 247 248…”
Section: Future Research Directionmentioning
confidence: 99%
“…1 and Supplemental Animation S1). Thus dynamic strain is minimal in normal alveoli (15,16,45). Loss of surfactant function with acute lung injury renders alveoli unstable, greatly reducing the alveolar collapse time constant, resulting in a rapid collapse of the alveolus with each expiration (58; Fig.…”
Section: Pathophysiology Of Vilimentioning
confidence: 99%